Monitoring of soluble pectin content in orange juice by means of MIR and TD-NMR spectroscopy combined with machine learning - Bizzani, Marilia [UNESP]; William Menezes Flores, Douglas; Alberto Colnago, Luiz; David Ferreira, Marcos (Elsevier, 2020)
This study represents a rapid and non-destructive approach based on mid-infrared (MIR) spectroscopy, time domain nuclear magnetic resonance (TD-NMR), and machine learning classification models (ML) for monitoring soluble pectin content (SPC) changes in orange juice. Current reference methods of SPC in orange juice are laborious, requiring several extractions with successive adjustments hindering rapid process intervention. 109 fresh orange juices samples, representing different harvests, were analysed using MIR, TD-NMR and reference method. Unsupervised algorithms were applied for natural clustering of MIR and TD-NMR data in two groups. Analyses of variance of the two MIR and TD-NMR datasets show that only the MIR groups were different at 95% confidence for SPC average values. This approach allows build classification models based on MIR data achieving 85% and 89% of accuracy. Results demonstrate that MIR/ML can be a suitable strategy for the quick assessment of SPC trends in orange juices.
Keywords: Data science; Machine learning; MIR; Orange juice; Soluble pectin content (SPC); TD-NMR